Malaria situation and elimination in Africa with specific focus on Zimbabwe: a systematic review - Zakio Makuvara; Solomon R. Magano; Grace Mugumbate (Taylor & Francis Group, 2024)
Malaria is an infectious disease caused protozoa in genus Plasmodium. In spite of the efforts made in the fight against malaria, this tropic infectious disease is still one of the most common vector borne disease in the WHO African region. Therefore, this systematic review focuses on current malaria control interventions, treatment options and elimination in Africa with specific focus on Zimbabwe. The literature was searched in electronic databases such as PubMed, MEDLINE, ClinicalTrials.gov, DOAJ, Europe PubMed Central, Web of Science and Google Scholar. Furthermore, the literature search was expanded to include reference lists in peer-reviewed scientific publications. Some of the key phrases chosen in the literature search were 'malaria control interventions', 'Zimbabwe and malaria', 'Malaria treatment', 'Malaria prevalence in Zimbabwe', 'Malaria prevalence in Africa', 'malaria and Africa', and 'Africa and malaria therapy'. In this study, 185 articles were reviewed and literature was summarized in line with the objectives of the study. Based on literature survey, it was noted that intensification of malaria control interventions and treatment has led to a remarkable decline in malaria morbidity and mortality. However, malaria remains a public health concern in most African countries including Zimbabwe. This has been attributed to the (1) development of physiological and behavioral resistance among malaria vectors in response to insecticides overuse, (2) development of resistance in P. falciparum to antimalarial drugs, (3) migration of malaria tolerant and positive individuals from malaria endemic areas to settings where malaria is less common, (4) emergence of genetically distinct malaria parasites which has limited the development of an effective malaria vaccine and protective immunity.